Effects of a Four-Strain Probiotic on Gut Microbiota, Inflammation, and Symptoms in Parkinson's Disease : A Randomized Clinical Trial - Leta, Valentina; Zinzalias, Pavlos; Batzu, Lucia; Mandal, Gargi; Staunton, Juliet; Jernstedt, Frida; Rosqvist, Kristina; Timpka, Jonathan; van Vliet, Trinette; Trivedi, Dhaval; Podlewska, Aleksandra; Parry, Miriam; et al. (Movement Disorders, 2025)
Background: Gut dysbiosis and gut-brain-axis involvement in people with Parkinson's disease (PwP) support the use of gut-microbiota-modulating interventions. Probiotics may help manage constipation in PwP; however, mechanisms underpinning additional beneficial properties are unknown. Objective: The aim was evaluating the effects of a probiotic (Lacticaseibacillus rhamnosus, Lactobacillus acidophilus, Lactiplantibacillus plantarum and Enterococcus faecium) on gut microbiota, inflammation, motor and non-motor symptoms (NMS) in PwP and constipation. Methods: In this multicenter, randomized, double-blind, placebo-controlled trial (NCT05146921), PwP and constipation were randomized (1:1) to receive either the probiotic (4.08 × 108 CFU/mL) or placebo orally (70 mL/day) for 12 weeks. The primary endpoint was the differential abundance of gut microbiota taxa between baseline and end-of-treatment in the active versus placebo group. Secondary/exploratory endpoints included changes in inflammatory cytokines plasma levels, short-chain fatty acids (SCFAs) plasma and fecal levels, motor and NMS outcomes after 12 weeks. A per-protocol analysis was performed. Results: Between July 17, 2019 and February 6, 2022, 74 participants were randomized. Data from 35 (probiotic) and 33 (placebo) participants were analyzed. Enrichments of bacteria with beneficial health-related properties (Odoribacteraceae, Enterococcaceae, and Blautia faecicola) were observed in the active group compared to placebo (P ≤ 0.05). Proinflammatory cytokine TNF-α plasma levels decreased with probiotic treatment and increased with placebo (P < 0.05). No changes in SCFAs levels were observed. Reductions in time-to-on and NMS scale scores (P < 0.05) were observed only in the active group. Conclusions: This probiotic was effective in beneficially enriching the gut microbiota with potential to reduce systemic inflammation, shortening time-to-on following levodopa administration, and alleviating NMS burden in PwP experiencing constipation.
Publisher Copyright: © 2025 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.
Keywords: gut microbiota; inflammation; motor symptoms; non-motor symptoms; Parkinson's disease; probiotics